2020
DOI: 10.1002/bsd2.131
|View full text |Cite
|
Sign up to set email alerts
|

Does financial development influence fertility rate in South Asian economies? An empirical insight

Abstract: The purpose of this paper is to empirically investigate the effect of financial development on fertility rate along with other major indicators in select South Asian economies over the period 1990-2016. The study uses various statistical techniques such as Johansen-Fisher panel co-integration approaches are employed to examine the long-run relationship among the variables and for statistically quantile regression is employed. The study finds that the variables under consideration are found to be cointegrated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Moreover, the relationship between financial development and fertility is different for different countries at different development levels. They found that financial development tends to increase fertility in developed countries, but has an opposite effect in developing countries (Habibullah et al, 2016;Sethi et al, 2021). In developing countries, the relationship between financial development and the total fertility rate is a non-linear inverted Ushaped relationship, while in developed countries it is a non-linear U-shaped relationship Lai and Yip (2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, the relationship between financial development and fertility is different for different countries at different development levels. They found that financial development tends to increase fertility in developed countries, but has an opposite effect in developing countries (Habibullah et al, 2016;Sethi et al, 2021). In developing countries, the relationship between financial development and the total fertility rate is a non-linear inverted Ushaped relationship, while in developed countries it is a non-linear U-shaped relationship Lai and Yip (2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The interplay between socioeconomic changes, financial development and fertility trends has garnered significant attention from researchers and policymakers alike. Studies by Sethi et al (2021) and Idris et al (2018) have demonstrated that financial development has decreased fertility rates in the South Asian Region.…”
Section: Introductionmentioning
confidence: 99%
“…Fertility issues have always been a global concern, and it was estimated that between 48 million couples and 186 million individuals have infertility [ 1 ]. With the development of economy and society, the fertility rate shows a trend of negative correlation [ 2 , 3 ]. In developed countries, the potential adverse consequences of chronically below-replacement-level fertility rate have been widely discussed [ 4 ].…”
Section: Introductionmentioning
confidence: 99%